Biotechnological treatment of microalgae enhances growth performance, hepatic carbohydrate metabolism and intestinal physiology in gilthead seabream (Sparus aurata) juveniles close to commercial size - Molina-Roque, Luis (2022)
The aim of this work was to evaluate the effects on growth performance, intermediary metabolism and welfare of the inclusion of two commercial microalgae-based ingredients called LB-ChromaBream (LB-CB) and LB-ChromaBream-plus (LB-CBplus) in the diet of gilthead seabream (Sparus aurata) close to commercial size. For this purpose, fish of similar to 182 g of initial body mass were fed to satiety (ad libitum) for 41 days with three different diets: (i) CONTROL diet (CTRL), with a commercial-like formulation; (ii) LB-CB diet, with a 10 % inclusion of microalgal product; (iii) LB-CBplus diet, with a 10 % inclusion of the same product but enzymatically hydrolysed to increase the bioavailability of the nutrients. The results obtained show that the use of these microalgal products leads an overall improvement in productive parameters in terms of growth (15 % in SGR) and feed efficiency (11 %), as well as a significant reduction in circulating cortisol with the LB-CBplus diet. Observations on plasma and liver metabolites, and particularly on hepatic metabolic enzymes, collectively indicate that microalgae supplementation of feed lead to a better use of carbohydrates as a source of energy in the liver and other tissues, potentially sparing triglycerides within this tissue, and a channelling hepatic triglycerides to fuels growth. Finally, the specimens fed the supplemented diets experienced a substantial improvement in intestinal health, achieved by longer intestines, a higher transepithelial resistance and better apparent permeability measured by electrophysiological methods, especially those fed LB-CBplus, which could explain the increase in productive performance by improving nutrient assimilation. In conclusion, this study shows that the experi-mental feeds, especially the one containing biotechnologically treated microalgae, are suitable for improving some important indicators of growth performance and physiological condition of gilthead seabream, thus revealing the potential for their inclusion in new functional feeds for this species at an advanced stage of the production cycle.